15N‐Permethylated amino acids as efficient probes for MRI‐DNP applications. (6th June 2013) - Chiavazza, Enrico; Viale, Alessandra; Karlsson, Magnus; Aime, Silvio
Abstract : The synthesis, NMR properties and preliminary polarization tests on protonated and perdeuterated forms of α‐trimethylglutamine (NMe3 Gln), α‐trimethylglutamate (NMe3 Glu) and ε ‐trimethyllysine (NMe3 Lys) are reported. The 15 N‐permethylated, perdeuterated amino acids display very long 15 N‐ T 1 values, ranging between 190 and 330 s, are well polarized by the dynamic nuclear polarization (DNP) procedure, yielding good polarization levels (10%), and appear to be well tolerated by cells and mice. The obtained results make perdeuterated amino acids excellent candidates for innovative DNP 15 N‐MRI applications such as perfusion or targeting studies. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : 15 N‐permethylated, perdeuterated amino acids display very long‐T1 values for the (CD3 )3 15 N resonances thus representing particularly suitable substrates for applications such as perfusion or targeting studies.